2020
DOI: 10.1177/2325967120959654
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play and Performance After Primary ACL Reconstruction in American Football Players: A Systematic Review

Abstract: Background: Anterior cruciate ligament (ACL) injuries are among the most common sports-related injuries, and they can have a negative impact on players’ ability to return to play (RTP). There is a paucity of literature focused on RTP after ACL reconstruction (ACLR) in collision sports. Purpose: To characterize the impact that an ACL injury has on the ability to RTP and the post-ACLR performance level in American football players. Study Design: Systematic review; Level of evidence, 4. Methods: An electronic sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…ACL tears are catastrophic and common injuries in football, with athletes estimated to have a ten times higher risk of rupture in participation when compared to other sports[ 2 ]. A recent systematic review reported the overall return to play rate in NFL athletes after an ACL tear at only 67.2%, with significant variability depending on the position and experience of the athlete[ 3 - 5 ]. Additionally, of players able to return, the financial impact of these injuries on player earning potentials is well documented, with salary losses of roughly $2 million per year after injury[ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…ACL tears are catastrophic and common injuries in football, with athletes estimated to have a ten times higher risk of rupture in participation when compared to other sports[ 2 ]. A recent systematic review reported the overall return to play rate in NFL athletes after an ACL tear at only 67.2%, with significant variability depending on the position and experience of the athlete[ 3 - 5 ]. Additionally, of players able to return, the financial impact of these injuries on player earning potentials is well documented, with salary losses of roughly $2 million per year after injury[ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…ACL tears are rather common, but they are perceived as serious injuries, which may significantly impact the career of athletes due to the recovery times required and to the risk of not restoring in full the pre-injury status of the knee. 49,50 Results following ACL surgery are extremely satisfactory but current evidence suggests that, besides the role of patient's individual risk factors, no specific technique, no graft choice, and no fixation device is able to provide superior outcomes. 51,52 Therefore, biologic augmentation soon came into play: as expected, the literature revealed that PRP-products are the most commonly used in this particular field, due to their easier preparation protocol and lower costs compared to cell-based approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior cruciate ligament (ACL) injuries are very common in sports [1]. The most important goal for athletes after ACL reconstruction is a successful return to play [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Anterior cruciate ligament (ACL) injuries are very common in sports [1]. The most important goal for athletes after ACL reconstruction is a successful return to play [1,2]. It has been reported that from 78% to 98% of professional athletes, and 65% of amateurs, return to pre-injury level [3].…”
Section: Introductionmentioning
confidence: 99%